1996
DOI: 10.1021/jp9536211
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CO in Rh6(CO)16/NaY Clusters and Isolated Rh+(CO)2/NaY by Solid-State 13C NMR Spectroscopy

Abstract: Solid-state NMR spectroscopy of 13 C is used to structurally characterize and quantify carbonyl groups in Rh 6 (CO) 16 and Rh + (CO) 2 complexes entrapped in NaY zeolite. MAS NMR line shape simulations show that the dicarbonyl groups present in Rh 6 (CO) 16 and Rh + (CO) 2 have the same shielding parameters (σ iso ∼ 178 ppm, CSA ∼ 400 ppm, and η ∼ 0.2) but exhibit greatly different spin-lattice relaxation rates. Bridged groups exist only in clusters and are bonded to three Rh atoms. Their shielding parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 21 publications
3
14
0
Order By: Relevance
“…Although the linear CO in Rh 6 (CO) 16 and Rh + (CO) 2 are not directly resolved via the isotropic shift, the NMR spin−lattice relaxation times T 1 of these two terminal groups differed by 2 orders of magnitude, which allowed for their quantitative determination. The quantitative analysis yielded the Rh 6 :Rh + ratio of 3:1 for a 4 wt % Rh sample and 1:1 for a 6 wt % Rh sample . The intensity ratio of the linear CO to the bridging CO in the rhodium clusters was found to be 2.9(±0.2):1, in good agreement with the stoichiometry of the cluster molecule.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…Although the linear CO in Rh 6 (CO) 16 and Rh + (CO) 2 are not directly resolved via the isotropic shift, the NMR spin−lattice relaxation times T 1 of these two terminal groups differed by 2 orders of magnitude, which allowed for their quantitative determination. The quantitative analysis yielded the Rh 6 :Rh + ratio of 3:1 for a 4 wt % Rh sample and 1:1 for a 6 wt % Rh sample . The intensity ratio of the linear CO to the bridging CO in the rhodium clusters was found to be 2.9(±0.2):1, in good agreement with the stoichiometry of the cluster molecule.…”
Section: Resultsmentioning
confidence: 53%
“…Characterization of Rh 6 (CO) 16 /NaY by FTIR and 13 C MAS NMR . Detailed FTIR and 13 C MAS NMR studies of the structure of Rh 6 (CO) 16 /NaY were reported previously. , To facilitate the interpretation of spectroscopic data presented in this work for Rh c /NaY and Rh(imp)/NaY, we first briefly summarize these earlier results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 C solid‐state nuclear magnetic resonance (SSNMR) experiments have proven to be a valuable probe of CO dynamics, binding strength, and local structure in many compounds. 13 C SSNMR spectroscopy has been used to study the binding affinity and rigidity of CO and CO 2 in copper‐based MOFs,11 along with the local environments, exchange, and binding modes of CO in a rhodium‐exchanged NaY zeolite 12. The adsorption of CO within H‐Y zeolites13 has been probed by 13 C SSNMR spectroscopy, which was also used to understand the role of CO in the carbonylation of alcohols and olefins in the zeolite H‐ZSM‐514 and in the catalytic conversion of methanol to hydrocarbons on unmodified ZSM‐5 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Because some of the clusters may have been oxidatively fragmented after being adsorbed on the MgO surface (by reaction, e.g., with surface OH groups) to give the rhodium subcarbonyls, , the resultant cationic species would be expected to be in close proximity to each other. Therefore, weak metal−metal interactions might be detected by EXAFS spectroscopy at both the Pt and Rh edges.…”
Section: Discussionmentioning
confidence: 99%